2021
DOI: 10.3390/ijms22147691
|View full text |Cite
|
Sign up to set email alerts
|

Large Rab GTPases: Novel Membrane Trafficking Regulators with a Calcium Sensor and Functional Domains

Abstract: Rab GTPases are major coordinators of intracellular membrane trafficking, including vesicle transport, membrane fission, tethering, docking, and fusion events. Rab GTPases are roughly divided into two groups: conventional “small” Rab GTPases and atypical “large” Rab GTPases that have been recently reported. Some members of large Rab GTPases in mammals include Rab44, Rab45/RASEF, and Rab46. The genes of these large Rab GTPases commonly encode an amino-terminal EF-hand domain, coiled-coil domain, and the carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Rab44 is a member of the large Rab GTPase family that encodes an N-terminal EF-hand domain, a coiled-coil domain, and a C-terminal Rab-GTPase domain with a molecular mass of approximately 110 kDa [ 14 , 15 ]. Previously, our research group had initially identified an upregulated Rab44 protein during osteoclast differentiation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rab44 is a member of the large Rab GTPase family that encodes an N-terminal EF-hand domain, a coiled-coil domain, and a C-terminal Rab-GTPase domain with a molecular mass of approximately 110 kDa [ 14 , 15 ]. Previously, our research group had initially identified an upregulated Rab44 protein during osteoclast differentiation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…When bound to its respective receptors on the surface of the endoplasmic reticulum (ER), IP 3 promotes a transient release of Ca 2+ from ER stores and a subsequent increase in cytosolic Ca 2+ concentrations 4 . This initial wave of Ca 2+ mobilization is essential for mast cell degranulation, a process reliant on SNARE fusion proteins which require Ca 2+ ‐sensitive accessory proteins such as Rab GTPases and synaptotagmins 5,6 . This sustained elevation in cytosolic Ca 2+ concentrations is also essential for the activation of critical proinflammatory transcription factors such as nuclear factor‐κB (NFκB) and nuclear factor of activated T cells (NFAT) and the subsequent secretion of various cytokines and chemokines, 7–9 augmenting the early phase allergic response.…”
Section: Introductionmentioning
confidence: 99%
“…Rab proteins are classified into two groups: conventional “small” Rab proteins, including Rab1‐43, and atypical “large” Rab proteins, including Rab44, Rab45/RASEF, and Rab46 13–16 . The former members encode the Rab domain and exhibit molecular weights of approximately 20–30 kDa.…”
Section: Introductionmentioning
confidence: 99%